1997
DOI: 10.1007/bf02055433
|View full text |Cite
|
Sign up to set email alerts
|

Coexpression of Bcl-2, c-Myc, and p53 oncoproteins as prognostic discriminants in patients with colorectal carcinoma

Abstract: These findings suggest that oncoprotein coexpression possesses significant prognostic and potential therapeutic value; incorporation of molecular markers into future prospective randomized trials is advisable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
1
5

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 17 publications
3
30
1
5
Order By: Relevance
“…Positive staining for c-myc was found in 71% and 65% of patients, respectively, and was not associated with Dukes' stage or histological grade in either study (Miller et al, 1992;Bhatavdekar et al, 1997). A significantly better overall survival was observed in the 17 patients without c-myc staining, when compared with the 31 with positive staining in the smaller study (Bhatavdekar et al, 1997).…”
Section: C-mycmentioning
confidence: 78%
See 1 more Smart Citation
“…Positive staining for c-myc was found in 71% and 65% of patients, respectively, and was not associated with Dukes' stage or histological grade in either study (Miller et al, 1992;Bhatavdekar et al, 1997). A significantly better overall survival was observed in the 17 patients without c-myc staining, when compared with the 31 with positive staining in the smaller study (Bhatavdekar et al, 1997).…”
Section: C-mycmentioning
confidence: 78%
“…Immunohistochemical analysis of c-myc protein in colorectal tumours has been evaluated in two separate studies [n = 118, Dukes' A, 7; B, 35; C, 41; D, 35 (Miller et al, 1992) and n = 48, Dukes' B, 24; C, 24 (Bhatavdekar et al, 1997)]. Positive staining for c-myc was found in 71% and 65% of patients, respectively, and was not associated with Dukes' stage or histological grade in either study (Miller et al, 1992;Bhatavdekar et al, 1997).…”
Section: C-mycmentioning
confidence: 99%
“…[28][29][30][31] For example, Bcl-2 expression was associated with favorable outcome in stage II colon cancer. Some studies showed either no correlation between Bcl-2 expression and survival, or that overexpression of Bcl-2 correlated with an unfavorable outcome in colorectal cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed either no correlation between Bcl-2 expression and survival, or that overexpression of Bcl-2 correlated with an unfavorable outcome in colorectal cancer patients. [28][29][30][31] The clinical utility is not yet verified. In this study, we provide novel evidence to demonstrate that the interaction of PXN with Bcl-2 promotes Bcl-2 protein stability via phosphorylation of PXN at S272 and Bcl-2 at S87 by pPXN-Y31/Y118-mediated PAK1 and ERK activation, and this Bcl-2 protein stability confers 5-FU resistance in cells and xenograft tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors (3) had demonstrated that bcl-2 overexpression seems to be associated with advanced histological grade, resulting in a more aggressive tumour. Others (2,4,9,14,24) had showed that patients with bcl-2 positive colorectal carcinoma had a more favourable clinical course.…”
Section: Discussionmentioning
confidence: 99%